Diskursus Hermeneutika dan Kritik Terhadap Studi Qur’an Kontemporer - Sarah Busyra (Transformatif, 2021)
Hermeneutic discourse is one of the leading issues in the postmodern studies. Since hermeneutics was arisen from Christian history towards the Bible, it has undergone many developments and has even been used as a method of interpreting the Qur’an by some Muslim scholars. In this article, the researcher not only tries to review the hermeneutics, its history as well as its characters but also to criticize contemporary Qur'an studies by Muslim scholars which was adopting hermeneutic theory. This research is a Library Research and applicated the descriptive analysis method for data analyzing. The researcher finds criticism that hermeneutics is unable to interpret the Qur'an objectively as its purpose. It is due to the West’s principles, beliefs and views of life are incompatible with the Islamic worldview.